Cochlear morphology of Indonesian Homo erectus from Sangiran. Issue 165 (April 2022) - Urciuoli, Alessandro; Kubat, Jülide; Schisanowski, Lisa; Schrenk, Friedemann; Zipfel, Bernhard; Tawane, Mirriam; Bam, Lunga; Alba, David M.; Kullmer, Ottmar
Abstract: Homo erectus s.l. is key for deciphering the origin and subsequent evolution of genus Homo . However, the characterization of this species is hindered by the existence of multiple variants in both mainland and insular Asia, as a result of divergent chronogeographical evolutionary trends, genetic isolation, and interbreeding with other human species. Previous research has shown that cochlear morphology embeds taxonomic and phylogenetic information that may help infer the phylogenetic relationships among hominin species. Here we describe the cochlear morphology of two Indonesian H. erectus individuals (Sangiran 2 and 4), and compare it with a sample of australopiths, Middle to Late Pleistocene humans, and extant humans by means of linear measurements and both principal components and canonical variates analyses performed on shape ratios. Our results indicate that H. erectus displays a mosaic morphology that combines plesiomorphic (australopithlike) features (such as a chimplike round cochlear cross section and low cochlear thickness), with derived characters of later humans (a voluminous and long cochlea, possibly related to hearing abilities)—consistent with the more basal position of H. erectus . Our results also denote substantial variation between the two studied individuals, particularly in the length and radius of the first turn, as well as cross-sectional shape. Given the small size of the available sample, it is not possible to discern whether such differences merely reflect intraspecific variation among roughly coeval H. erectus individuals or whether they might result from greater age differences between them than currently considered. However, our results demonstrate that most characters found in later humans were already present in Indonesian H. erectus, with the exception of Neanderthals, which display an autapomorphic condition relative to other Homo species.